Molecular Identification of Fungi Isolated from Indonesian Coal using ITS Region Sequence - Shinta Wulansari; Fitri Widya Handayani; Muhammad Shobihul Khoir (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Fungi represent a highly diverse group of microorganisms found in various environments, including extreme habitats such as coal deposits. This study aimed to identify fungal species isolated from Indonesian coal based on ITS region sequence analysis and compare the effectiveness of CTAB/NaCl and microwave methods for fungal DNA isolation from coal substrates. Fungal isolates were obtained from coal samples using the dilution method on PDA media. DNA isolation was performed using CTAB/NaCl and microwave methods with power levels 700 W. ITS region amplification used PCR with ITS5-ITS4 primers. Sequence analysis was conducted using BLASTn and phylogenetic reconstruction using the Neighbor-Joining method with 1000x bootstrap replicates. Two fungal isolates (isolate A and B) were obtained, with only isolate A further characterized. Morphological observations showed characteristics similar to the genus Penicillium. The CTAB/NaCl method successfully yielded DNA with purity of 2.01 and concentration of 275.89 ng/µL, producing a single DNA band on electrophoresis. Conversely, the microwave method failed to isolate intact DNA across high power, indicated by absence of DNA bands despite spectrophotometric purity values (2.02-3.28) falling within acceptable range. ITS region amplification of isolate A successfully produced a 592 bp product. BLASTn analysis revealed isolate A shared 94% identity with several Penicillium species. Phylogenetic analysis demonstrated isolate A was closely related to Penicillium sublateritium JX841245.1 (94.66% identity; 68% bootstrap support). The identity value below 97% suggests isolate A has potential as a novel or cryptic species within genus Penicillium. This study represents the first report on molecular identification of fungi from Indonesian coal and comparison of DNA isolation methods on this substrate. The CTAB/NaCl method proved superior to the microwave method for fungal DNA isolation from coal. Further analysis with additional genetic markers is needed to confirm the taxonomic status of isolate A.